Housing Tenure, Housing Satisfaction, and Fertility Intentions in the Nordic Context of the Early 2020s - Li, Yuting (My University, 2025)
The declining fertility rate in Nordic countries since the 2010s has challenged previous fertility theories. Among the many factors, housing has become increasingly recognized as a crucial determinant of family formation and reproductive decisions. In Nordic countries, where housing systems vary despite shared welfare-state characteristics, the recent relationship between housing and fertility outcomes remains underexplored, particularly from a comparative perspective. Using microdata from the Generations and Gender Survey - Round 2 Wave 1 for Finland, Sweden, Norway, and Denmark (n = 14,573), this research investigates whether housing tenure and individuals’ perceived housing satisfaction relate to fertility intentions, employing logistic regression models. It further examines whether these associations vary across the Nordic countries, among different age groups, and by parity. Results indicate that homeownership is positively associated with fertility intentions across the Nordic countries, with the exception of Denmark, where it is negatively associated. This divergence may reflect Denmark’s tenure-neutral housing policies and extensive provision of social rental housing, potentially reversing the link between homeownership and childbearing. The positive association between homeownership and fertility intentions is particularly evident among younger individuals and those without children. Meanwhile, housing satisfaction shows a negative association with fertility intentions, a pattern more pronounced among younger respondents and in Denmark and Sweden compared to Finland and Norway. This may suggest that higher levels of housing satisfaction reflect lifestyle preferences, larger investments into living standards, or a lower perceived urgency to transition into parenthood. This research contributes to the broader discussion on the current low levels of fertility in the Nordic countries by examining the role of housing. Drawing on the most recent survey data, it introduces perceived housing satisfaction as a complementary dimension to conventional housing tenure measures. Through comparative analysis within the Nordic context, the study offers a more nuanced understanding of how housing conditions relate to fertility intentions across different institutional and demographic settings.
Keywords: Low fertility, housing tenure, housing satisfaction, Nordic countries